Bifidobacterium longum subsp. longum dipro-O: a potential therapeutic agent for ameliorating metabolic disorders in high-fat diet-induced obesity mouse model - Xu, Ning; Luo, Jiang; Chen, Weiyang; Xiang, Weiwei; Zhai, Yue; Jiang, Wei; Wu, Junlin; Hao, Yanqing; Chen, Meiru; Yu, Qinghua (Frontiers in Endocrinology, 2025)
BackgroundExcessive fat intake results in lipid metabolic disorders accompanied by inflammation and other complications. However, the effectiveness of drug interventions for metabolic disorders is not ideal, owing to their inherent limitations. Here, we introduce the probiotic Bifidobacterium longum subsp. longum dipro-O, which ameliorates metabolic disorders without any side effects.MethodC57BL/6J mice were fed a 60% kcal high-fat diet (HFD) for eight weeks to induce obesity, and then dipro-O intervention was administered for nine weeks. Blood glucose, serum cholesterol, triglyceride, and high-density lipoprotein (HDL) levels were assessed, and liver sections were processed to evaluate fat accumulation.Intestinal barrier related gene and pro-inflammatory gene in colon were detected to analyze the ability of dipro-O in intestinal homeostasis remodeling and 16S rRNA sequencing was performed to assess the changes in intestinal microbial composition.ResultAfter eight weeks of obesity induction, probiotic interventions were initiated and lasted for 9 weeks. Compared to the HFD-PBS group, mice in the HFD-dipro-O group gained less body weight and showed a statistically significant improvement in blood glucose control. Similarly, serum cholesterol and triglyceride levels were significantly reduced, while serum HDL was elevated, and liver sections showed that dipro-O intervention decreased fat accumulation and injury levels in the liver. Functional enrichment analysis revealed that changes in the gut microbiota inhibited bacterial invasion of epithelial cells.ConclusionDipro-O effectively reduced HFD-induced obesity by decreasing body weight gain, serum lipid marker levels, and liver fat accumulation. QPCR and 16S rRNA sequencing data indicated that dipro-O intervention promoted intestinal homeostasis maintenance. Taken together, these findings indicate that dipro-O has the potential to intervene in lipid disorders as an alternative to drug therapies.